Respon Beberapa Genotipe Kedelai Terhadap Tingkat Cekaman Kekeringan Tanah Ultisol - , Hapsoh; Sudirman Yahya; T. M. H. Oelim; Didy Sopandie (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
This research was aimed to find out the tolerant and susceptible soybean genotypes to drought stress. Twenty two genotypes were tested on three levels of drought stress, based on soil moisture conditions: 80% of field capacity (FC ), 60% FC and 40% FC. The experiment was conducted in plastic house at the experimental field of Meteorological Station, Sampali, Medan, from February to May 2000. The results show that increasing on the severity of drought caused significantly reduced growth and yields, which indicated by the reduction on shoot dry weight, stem diameter, filled pod number, seed number/plant and seed dry weight. The level of growth and yield reductions varied 1 among genotypes. The highest variation was shown at the drought level of 60% FC. Sindoro and Lokon were selected as tolerant and susceptible genotypes, consecutively. It was concluded that the adaptation of tolerant plants strongly related to their ability to improve the root system and to reduce the transpiration surfaces. Key words: Soybean, Drought, Tolerant, Susceptible